Die Landmauer von Konstantinopel-Istanbul Historisch-topographische und baugeschichtliche Untersuchungen - Asutay-Effenberger, Neslihan (Millennium-Studien / Millennium Studies, 2008)
The land walls of Constantinople are one of the largest and most important defensive fortifications from Late Antiquity. The subject of this book are the history and topography of the Theodosian Land Walls and the Walls of Blachernae (the so-called walls of the XIVth region, the Komnenian Walls, the section between the Komnenian Walls and the Golden Horn). The central topics are the conception and planning of the Theodosian Walls, the chronology of the Walls of Blachernae, the date of the Golden Gate and the actual gateway of the outer gate, an investigation into the Byzantine names for the gates north of the re-discovered Romanos Gate, the identification of the Mermerkule castle and other localities, as well as an analysis and documentation of the structure itself.